2007
DOI: 10.1007/s00109-007-0157-6
|View full text |Cite
|
Sign up to set email alerts
|

Candidate biomarkers for discrimination between infection and disease caused by Mycobacterium tuberculosis

Abstract: Infection with Mycobacterium tuberculosis is controlled by an efficacious immune response in about 90% of infected individuals who do not develop disease. Although essential mediators of protection, e.g., interferon-gamma, have been identified, these factors are insufficient to predict the outcome of M. tuberculosis infection. As a first step to determine additional biomarkers, we compared gene expression profiles of peripheral blood mononuclear cells from tuberculosis patients and M. tuberculosis-infected hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
180
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 213 publications
(197 citation statements)
references
References 29 publications
12
180
2
3
Order By: Relevance
“…Previous studies using microarray analysis in TB patients have identified gene patterns, which identify subjects at risk for recurrent disease among patients with cured TB 25 and a distinct subset of genes to classify TB patients and LTBI in a Caucasian population. 17 TB patients and healthy household control subjects (both latently infected and uninfected) included in this study were recruited from a cohort with high incidence of infection and disease. Accordingly, the recruitment of NID proved difficult, as almost all individuals in this cohort were found to give a positive result in a tuberculin skin test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies using microarray analysis in TB patients have identified gene patterns, which identify subjects at risk for recurrent disease among patients with cured TB 25 and a distinct subset of genes to classify TB patients and LTBI in a Caucasian population. 17 TB patients and healthy household control subjects (both latently infected and uninfected) included in this study were recruited from a cohort with high incidence of infection and disease. Accordingly, the recruitment of NID proved difficult, as almost all individuals in this cohort were found to give a positive result in a tuberculin skin test.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study by our group had identified CD64 (alias FCGR1A; Fc gamma receptor 1A) as one of the highest ranking differentially expressed genes in TB-diseased versus latently infected Caucasian subjects. 17 Despite of their different annotations, these genes have remarkably similar sequences. The oligonucleotide probes on the microarray chips used in both studies, were 100% complementary to the sequences of the probes used in either study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only the heavy chain of ferritin has ferroxidase activity and therefore the anti-oxidant activity of ferritin is attributed only to the heavy chain subunit. The close association between H ferritin expression and the presence of necrosis suggests that H ferritin expression along with lactoferrin may be useful as a biomarker with prognostic or predictive value in determining the clinical outcome of tuberculosis (54).…”
Section: Discussionmentioning
confidence: 99%